Severe Hypertriglyceridemia Associated with Pegylated Asparaginase Successfully Treated with Plasma Exchange. (August 2022) - Cuevas, Rafael-Emmanuel; Cid, Joan; Carbonell-Ordeig, Sara; Álvarez-Larran, Alberto; Lozano, Miquel
Asparaginase (ASP), a chemotherapy treatment used for acute lymphoblastic leukemia (ALL), is known to provoke severe hypertriglyceridemia (HTG). We report the case of a woman with a history of obesity and diabetes mellitus who developed severe HTG (up to 7305 mg/dL) after receiving a pegylated form of ASP for ALL. The patient was treated with one plasma exchange without incident via peripheral veins using 5% albumin as a replacement solution. Her triglycerides were reduced to 485 mg/dL. A single plasma exchange was an efficient, fast, and safe way to decrease triglycerides concentration in plasma.